Geschichtsunterricht vor der Frage nach dem Sinn: Geschichts(unter)bewusstsein und die Optionen eines sinnzentrierten Unterrichts - Ammerer, Heinrich (2022)
The study investigates the historical-psychological anchor points of historical meaning generation as well as the universal unconscious motives by which people shape historical narratives. A distinction is made between epistemic (describing facts) and phronetic (describing courses of action) meaning, from which two different modes of viewing history can be derived, and for the latter the use of Jungian archetypes is suggested. From the theoretical explanations, pragmatic considerations for a more meaning-centered teaching of history are derived.